Gender Microaggressions and Learning Environments: The Role of Physical Space in Teaching Pedagogy and Communication. Issue 11 (1st November 2016) - Lester, Jaime; Yamanaka, Aoi; Struthers, Brice
ABSTRACT: Career and technical education (CTE) programs account for a large proportion of student enrollments in community colleges each year. While women tend to dominate CTE enrollments overall, they remain concentrated in historically feminized fields contrary to nontraditional occupations in which less than 25% of workers are females. Drawing on the emerging research on microaggressions and classroom learning environments, this classroom observation research project of more than 80 hours of observations with supplemental student interviews sought to further an understanding of why women are underrepresented in specific CTE fields. The findings of this study indicated two distinct aspects of the classroom environment that helped stew a culture of gender microaggressions: the instructor pedagogy and communication style, and the impact of physical space. Physical structure, instructor pedagogy, and communication create an environment that often emphasizes and perpetuates social norms connecting men and masculinity to CTE and science, technology, engineering, and math education (STEM), which historically have been male-dominated environments. Results from this study extend the research on microaggressions and learning environments and fill a significant gap on gender and CTE.